Integrated pyranometer for photovoltaic module measurement - Abdul Aziz, Mohamad Faiz Syazwan (2013)
This project presents the development of a handheld pyranometer which is integrated with temperature sensor modules using the application of Microcontroller PIC16F877A. The pyranometer employs a reference solar cell which is calibrated to measure the solar irradiance. Besides the pyranometer, two temperature sensor modules were introduced to measure ambient temperature and photovoltaic module temperature respectively. All measurements from the pyranometer and temperature modules were controlled by a Microprocessor PIC16F877A which provides programming strategy through basic C language. The algorithm was designed based on the calibrated solar cell and the temperature sensor modules and the measured values were displayed on an LCD display. The results show that the integrated pyranometer device has relatively similar measured values when compared to a commercial integrated pyranometer.